Synthesis of 3H-imidazo[4,5-b] pyridine with evaluation of their anticancer and antimicrobial activity - Shelke, Rohini Narayan; Pansare, Dattatraya Navnath; Pawar, Chandrakant Dhondiram; Deshmukh, Arun Khandu; Pawar, Rajendra Pandu; Bembalkar, Saroj Ram (European Journal of Chemistry, 2017)
Microwave assisted and conventional synthetic methods of new 6-bromo-2-(substituted)-3H-imidazo[4,5-b]pyridine and its derivatives are described, which were obtained in reduced reaction times, higher yields, cleaner reactions than previously described methods. All the synthesized compounds were characterized, and screened for their anticancer and antimicrobial activity. Among synthesized compounds 3b and 3k shows prominent antibacterial activity and compound 3f shows both antibacterial and antifungal activity. Compounds 3h and 3j shows prominent anticancer activity against the both breast cancer cell lines, MCF-7 and BT-474. These results suggest that the imidazo[4,5-b]pyridine moiety may serve as a new promising template for synthesis of anticancer and antimicrobial agents and further study is required for evaluation of their mechanism of action.